The Application of Nanomaterials in Agricultural Field - Archana S (International Journal of Modern Agriculture, 2021)
Nanomaterials are considered as materials having external dimension of 1-100 nanometers. Nanomaterials can be formed naturally or as by-products of combustion reactions or directly designed for a particular purpose. These materials can differ in their physical and chemical characteristics from their counterpart. Nanomaterials of various sizes and shapes have been created as a result of recent technological advancements. These breakthroughs will serve as the foundation for future engineering to produce new properties tailored to particular applications. Nanomaterials have been used successfully and safely in a variety of areas in the past, including food production, environmental science and medicine. Nanomaterials have the capacity to improve pathogen identification, plant safety, seed growth and germination, as well as detection of the herbicide residue or pesticide, according to the preliminary research. This paper summarizes nanomaterials' agricultural applications and their potential role in future agricultural development.